2018
DOI: 10.1016/j.chom.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages Provide an Early Mycobacterium tuberculosis Niche and Initiate Dissemination

Abstract: Mycobacterium tuberculosis (Mtb) infection is initiated in the distal airways, but the bacteria ultimately disseminate to the lung interstitium. Although various cell types, including alveolar macrophages (AM), neutrophils, and permissive monocytes, are known to be infected with Mtb, the initially infected cells as well as those that mediate dissemination from the alveoli to the lung interstitium are unknown. In this study, using a murine infection model, we reveal that early, productive Mtb infection occurs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
408
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(479 citation statements)
references
References 45 publications
(55 reference statements)
24
408
0
7
Order By: Relevance
“… A simplified model of various innate cells of macrophage origin participating during M. tuberculosis infection . In their naive stage, alveolar macrophages (AMs) that phagocytose the inhaled bacilli at alveoli exhibit an M2‐like phenotype that is more permissive for the growth of M. tuberculosis . With IFN‐γ‐mediated priming through T cells, AMs could also exhibit the M1‐like phenotype at the early stage of infection and restrict bacterial growth .…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“… A simplified model of various innate cells of macrophage origin participating during M. tuberculosis infection . In their naive stage, alveolar macrophages (AMs) that phagocytose the inhaled bacilli at alveoli exhibit an M2‐like phenotype that is more permissive for the growth of M. tuberculosis . With IFN‐γ‐mediated priming through T cells, AMs could also exhibit the M1‐like phenotype at the early stage of infection and restrict bacterial growth .…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 99%
“…In their naive stage, alveolar macrophages (AMs) that phagocytose the inhaled bacilli at alveoli exhibit an M2-like phenotype that is more permissive for the growth of M. tuberculosis. 42 With IFN--mediated priming through T cells, AMs could also exhibit the M1-like phenotype at the early stage of infection and restrict bacterial growth. 19 However, AMs eventually acquire an M2-like phenotype after inflammation progresses.…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 99%
“…The movement of cells between compartments is necessary for the clearance of certain pathogens, yet has also been shown to promote dissemination. For instance, a non‐IVM study recently reported that the movement of infected alveolar macrophages into the interstitium may drive the dissemination of Mycobacterium tuberculosis . Although an interesting hypothesis, IVM will be necessary to track the migration of these cells to demonstrate categorically that it is indeed the alveolar macrophages that migrate into the interstitium.…”
Section: Localized Infectionsmentioning
confidence: 99%
“…For instance, a non-IVM study recently reported that the movement of infected alveolar macrophages into the interstitium may drive the dissemination of Mycobacterium tuberculosis. 72 Although an interesting hypothesis, IVM will be necessary to track the migration of these cells to demonstrate categorically that it is indeed the alveolar macrophages that migrate into the interstitium. IVM imaging of live events such as this will help to improve our understanding of the dynamic host-pathogen interactions that take place during infection with different types of intracellular and extracellular bacteria.…”
Section: Localized Infections: Imaging the Lungmentioning
confidence: 99%
“…Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), latently infects roughly one-third of the world's population and causes 1-2 million deaths per year. The current paradigm of acute infection is that after an actively infected person aerosolizes infectious Mtb-containing particles, a naive individual inhales the bacteria that then traverse the respiratory tree to ultimately be phagocytosed by alveolar macrophages (Churchyard et al, 2017;Cohen et al, 2018). While this model can account for pulmonary TB, it is insufficient to explain some extrapulmonary forms of TB initiated by oropharyngeal infection and lacking evidence of concurrent pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%